2021
DOI: 10.3389/fpsyg.2021.543846
|View full text |Cite
|
Sign up to set email alerts
|

Feeling for the Other With Ease: Prospective Actors Show High Levels of Emotion Recognition and Report Above Average Empathic Concern, but Do Not Experience Strong Distress

Abstract: Differences in empathic abilities between acting, dance, and psychology students were explored, in addition to the appropriateness of existing empathy measures in the context of these cohorts. Students (N = 176) across Higher Education Institutions in the United Kingdom and Europe were included in the online survey analysis, consisting of the Reading the Mind in the Eyes (RME) test, the Interpersonal Reactivity Index (IRI), the Empathy Quotient (EQ), and the E-drawing test (EDT), each measuring particular face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…While previous studies that have assessed empathy with different scales, have found it related to unmasked facial emotion recognition accuracy (Besel and Yuille, 2010; Israelashvili et al, 2019; Laukka et al, 2021), others that have used the IRI reported significant but inconsistent results (Laukka et al, 2021; Schlegel et al, 2019; Ventura et al, 2023). For example, Beals et al (2022) reported a positive association between fantasy scale scores and recognition of fear in facial expressions in typical participants, while Schmidt et al (2021) found higher fantasy scale scores related to better scores in emotion recognition in actors when compared to dancers and psychologists. These results suggest that the tendency to use the imagination to take the perspective of a fictional character may improve emotion recognition ability.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies that have assessed empathy with different scales, have found it related to unmasked facial emotion recognition accuracy (Besel and Yuille, 2010; Israelashvili et al, 2019; Laukka et al, 2021), others that have used the IRI reported significant but inconsistent results (Laukka et al, 2021; Schlegel et al, 2019; Ventura et al, 2023). For example, Beals et al (2022) reported a positive association between fantasy scale scores and recognition of fear in facial expressions in typical participants, while Schmidt et al (2021) found higher fantasy scale scores related to better scores in emotion recognition in actors when compared to dancers and psychologists. These results suggest that the tendency to use the imagination to take the perspective of a fictional character may improve emotion recognition ability.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by Pick et al (2019) showed that research regarding the understanding of empathic deficits in Parkinson’s is sparse and fragmented, despite its importance in the establishment of a functional doctor-patient relationship. With reference to the care-partners wellbeing, it is of interest to note people who engage in embodied and theoretical practices, such as theatre, show higher empathic skills without increased feelings of distress (e.g., Schmidt et al, 2021 ). Dance classes that emphasise a theatrical component could therefore be beneficial not only for people with Parkinson’s through the practice of gestures and facial expressions but also for their care-partner’s resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Even for the most studied dimension, empathy, convincing evidence that explains its causal link with acting remains absent (Winner, 2018), and the results of studies comparing the scores for empathy between groups of actors and non-actors do not consistently show higher scores among actors (Goldstein et al, 2009;Goldstein and Winner, 2012). Psychometric studies measuring performance in other dimensions of social abilities and social cognition further demonstrate that actors do not consistently show higher scores in these dimensions (Alfonso-Benlliure, 2021;Schmidt et al, 2021). Considering these studies showing that more acting experience does not necessarily bring about better scores in social abilities or social cognition, researchers have faced hardships in explaining the effect of the actual experience of acting.…”
Section: Introductionmentioning
confidence: 99%
“…Upon measuring the effects of representations of violence on spectators and performers, another study showed stronger emotional responses in the latter than in the first ( Berceanu et al, 2020 ). While examining the influence of acting experience on personality traits related to social abilities, as well as comparing the results for actors (exposed to different levels of acting training and embodied experience of theatrical performance) with those for the general population, academicians have found that professional actors have higher scores in extraversion, empathy, and theory of mind tasks than the general population and amateur actors ( Nettle, 2006 ; Goldstein and Winner, 2010 ; Schmidt et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%